(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Spina Bifida is a congenital defect that exposes the spinal cord to fluids in the womb. Severe cases of Spina Bifida can result in partial or complete paralysis, inability to walk, and/or bladder and bowel dysfunction. Surgeons perform in utero Spina Bifida repair to prevent the progressive damage to the exposed neural tissue before birth. As in utero Spina Bifida repair becomes the standard of care, pediatric neurosurgeons are exploring novel diagnostic and planning tools, like 3D segmentation and 3D printing, to prepare for the procedure and educate expecting parents.